DERADIKALISASI IDEOLOGI GERAKAN ISLAM TRANSNASIONAL RADIKAL - Syamsul Arifin; Hasnan Bachtiar (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
De-radicalization is an attempt to stem the rate of radicalism. The radicalism should be stemed due to its movement and thought both individual and group are oriented to radical activities, such as leading to violence, war and terror, which is very dangerous for mankind. However, thing need to be clarified are who is meant by this radical? What is the Islamic radicalism? In the Islamic context, the discussion is strongly related to the fundamental doctrines espoused by adherents, even become the ideology that stands firmly. Nonetheless, fundamentalism not necessarily lead to radicalism.